Optimization of the shading efficiency in the urban spaces in hot arid climate regions. (15th July 2019) - Khudhayer, Wael A.; Shaaban, Awni K.; Abdul Sukor, Nur Sabahiah
Abstract : Purpose: The contemporary urban fabrics in hot climate regions have overextended urban spaces that face problems of high heat stress due to intense solar radiation and air temperature and that cause the pedestrians to abandon the urban spaces due to thermal discomfort. This work introduced the shading effects as one of the prime factors that contribute to restore thermal comfort and attract pedestrian activities. The purpose of this paper is to identify the proportional limits of the urban space to maintain feasible shades for pedestrian activities. Design/methodology/approach: The urban space abstracted into a floor surrounded by four walls was then classified into four typologies. The assessment tool was developed to calculate the shading efficiency at the floor level of urban space. The width and the length of the floor equally was expanded in the range (0.5/0.5 to 4.0/4.0). The average shading efficiency of the expanded typologies was calculated along three intervals (Morning, midday and afternoon). The results were then analyzed, and critical guidelines were established that could be utilized in the design of the futuristic urban space and provide amendments to the existing urban space. Findings: The paper concluded that the performance of urban spaces was not due to the accumulative performances of all walls but rather due to the combination specific effective walls in response to the interactive variations shading patterns concerning daily pedestrian activities. Any large shallow urban space could be segmented into multiples of the recommended typologies by a vertical landscape. Originality/value: It is the first study that identified the expansion limit of the urban space that maintains feasible shades for the pedestrian. A further value of this study is establishing guidelines to the urban designers for the effective configurations of the urban space in terms of shading. These guidelines could be utilized in the design of the futuristic urban space and provide amendments to the existing urban space.